Cystic tuberculosis of talus in a child: A case report - Kumar, Akhilesh; Boruah, Tankeswar; Shaina, Sandeep; Kumar, Sapan (Indian Journal of Case Reports, 2020)
Tuberculosis of the talus is an unusual presentation of musculoskeletal tuberculosis. It is a rare manifestation of extra-pulmonary tuberculosis (EPTB) and accounts for around 0.1 to 0.3% of total EPTB. Its indolent nature often leads to missed or delayed diagnosis. Thus, prompt diagnosis is of utmost importance as diagnostic and therapeutic delay can worsen the prognosis. We are reporting a case of an 8-year-old boy with tuberculosis of the isolated right Talus with discharging sinus. The X-ray showed a cystic form of tuberculosis. He was treated with first-line antitubercular drugs. The child responded to the chemotherapy and by the end of the12-month course, he was asymptomatic. Thus, early diagnosis and therapy are crucial for good results.